Eco-hotel Router Fichermen del municipio de Bahía Solano (2022)
The project seeks to implement different types of resource savings that allow the user to live the experience of environmental awareness through an ecological hotel. It is solved from the principles of permaculture, a concept that allows to have an absolute natural and sustainable lifestyle, however, local support is key, that is why the hotel has a fishing orientation, which allows to involve the tourist and the local contributing to the economy of the municipality.